Does effectiveness of skill in complex I predict win in men`s Olympic volleyball games? - Zetou, E.; Moustakidis, A.; Tsigilis, N.; Komninakidou, A. (Journal of Quantitative Analysis in Sports, 2007)
The aim of the present study was to present the playing characteristics of the teams in complex I and to attempt to determine which of these characteristics led to victory and to the final ranking of the teams. The subjects were 38 Olympic Volleyball men's games. In every game, teams were characterized according to the result of the game (win or lose). The games were video-recorded and analyzed with the "Data Volleyball Project Sport Software" program. It recorded every skill of the complex I of the game, for each player of each team. There was a five level scale protocol according to the effectiveness of the skill (Eom & Schutz, 1992; Eom, 1989). Discriminant analysis was conducted to select which subset of the measured variables significantly contributed to the prediction of winning or losing in Olympic Volleyball teams. Among the five variables of service-reception: two variables "best reception, 1st set attack" and "Good reception, high set attack" were entered into the final model yielding, standardized coefficient 1.22 and .78 respectively. Among the five "attack from reception" categories, only one variable, "ace-point" was selected to enter into the final model. These results conclude that the "best" and "good reception" and the "ace-point" in the attack remain powerful aggressive tools for high level teams and were predictors to win.